PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH AND GAME UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SEJARAH PADA SISWA KELAS XI E SMAN 2 SINGARAJA SEMESTER GANJIL TAHUN AJARAN 2025/2026 - Royyan Khoirul Akbar, Dyka; Sedana Arta, Ketut; Made Oka Purwanti, Desak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of implementing the cooperative learning model of the Make a Match type combined with educational games in improving students’ motivation and learning outcomes in history subjects. The background of this study is the low level of students’ understanding of historical material, the majority of students’ initial scores being below the Minimum Mastery Criteria (KKM), and the low level of student engagement due to the dominance of conventional lecture-based teaching methods. This research is a Classroom Action Research (CAR) conducted in two cycles, consisting of planning, action, observation, and reflection stages. The subjects of this study were 40 students of class XI E at SMA Negeri 2 Singaraja in the first semester of the 2025/2026 academic year. Data were collected through observation, learning outcome tests, and questionnaires measuring students’ motivation and responses. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed improvements in all indicators. Students’ learning motivation increased from an average score of 25.62 in the first cycle to 38.3 in the second cycle, categorized as very high. Students’ learning outcomes also improved from an average score of 79.81 in the first cycle to 86.45 in the second cycle, with a learning mastery level reaching 100%. In addition, students’ responses to the learning model improved from an average score of 20.75 in the first cycle to 29.27 in the second cycle, categorized as very positive. In conclusion, the implementation of the Make a Match cooperative learning model combined with educational games is effective in creating an active, interactive, and enjoyable learning environment, as well as improving students’ motivation and learning outcomes in history learning.